Thermodynamic dislocation theory of adiabatic shear banding in steel. (May 2018) - Le, K.C.; Tran, T.M.; Langer, J.S.
Abstract: The statistical-thermodynamic dislocation theory developed in our earlier studies is used here in an analysis of the experimental observations of adiabatic shear banding in steel by Marchand and Duffy (1988). Employing only a small set of physics-based parameters, we are able to explain experimental stress-strain curves, including yielding transitions and strain hardening, over wide ranges of temperatures and strain rates. We make a simple model of weak notch-like perturbations that, when driven hard enough, trigger shear banding instabilities that are quantitatively in agreement with those seen in the experiments. Graphical Abstract: